Heat stress in sport - Wood, T. (Medicine and Science in Tennis, 2008)
In January 2008, the Journal of Science and Medicine in Sport produced a special issue on heat stress in sport. Co-edited by John Brotherhood and Tim Noakes the articles within it contained some original research in this area, as well as giving an overview of the current scientific knowledge and areas where further research was necessary.